Attacks Against Civilian Objects: An Analysis Under International Humanitarian Law - Salem Aessa Farhat; Rohaida Nurdin; Salawati Bit Basir (Faculty of Law, Hasanuddin University, 2022)
Civilian airports in recent internal armed conflict are being affected by the military operations of state armed forces and non-state armed groups. A review of the recent internal armed conflict in the middle east shows increase attacks on airports, which often disrupts, altogether halts civilian navigation, and increase the risk of being affected despite the fact that international humanitarian law (IHL) does prohibit such civilian objects attack that violates humanitarian law except in certain situations when it became military objectives. Moreover, military use of airport, may not justify any attack and remains prohibited by other IHL principles. Despite the negative use of civilian airports by the military as a justification to legalize attacking airports, IHL framework restricts this practice. States did not enact national prohibitions or restrictions of military use or limit attacks against civilian airports. However, recent armed conflict indicates that states can counter violation of the protections provided to civilian objects while military use by prohibiting military use of civilian airport. This article argues that states should enact and implement the exceptional rules to attack civilian buildings and forbid military use of civilian airports.